An evaluation of the effects of different pH levels and multiple firing temperatures on hardness of ceramic (Mustansiria Dental Journal, 2019)
This study was conducted to evaluate the effect of three different media( artificial saliva, acidic and alkaline ) and the effect of five times of multiple firingprocedure on hardness number of IPS e - max pressable ceramic .Seventy discs shaped specimens were fabricated according to the manufacturer’sinstructions. The specimens were randomly divided into seven groups. Three fordifferent media and four for multiple firing procedure ( ten specimens for eachgroup).The groups were subdivided as follows: According to different media:Group 1: specimens will be left in artificial saliva (Neutral media) for 10 days at 37c°in an incubator,Group2: specimens will be left in an acidic media for 10 days at 37c° in an incubator,Group 3: specimens will be left in an alkaline media for 10 days at 37c° in anincubator.According to multiple firing proceduresGroup 1: specimens will be exposed to firing one time,Group 2: specimens will be exposed to firing 3 times,Group 3: specimens will be exposed 5 times to firing procedures,Group 4: these specimens will be exposed to firing for 7 times.Then each group will be subjected to hardness test using Shore D hardness tester.The statistical analysis of the data of the tested groups of different media revealed thatthe high hardness values was in the alkaline media, while the lowest hardness valueswas in the acidic media. The highest hardness values of the firing groups were foundin the group of 7 times firing, while the lowest hardness values were found in thegroup 3 times firing and the results were statistically non significant.As a conclusion, an alkaline media increase the surface hardness of the IPS e –max ceramic, and multiple firing did not affect the surface hardness of the e –maxceramic